IoT-Based Automatic Sprinkler Innovation to Support Environmental Economic Sustainability in Tourism Aisles: English - Wahyudi; Sutasih Suhaeb; Wulan Purnamasari (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
Environmental management in Lorong Wisata requires innovative approaches to support economic and ecological sustainability. This research aims to design and implement an Internet of Things (IoT)-based automatic watering system to improve efficiency in plant management in the area. The system is designed using soil moisture sensors, microcontrollers, and an IoT platform to automate the watering process according to the needs of plants in real-time. Data collected from the sensors is integrated with web-based and mobile applications, enabling remote monitoring and control. Trial results showed that the system was able to optimise water usage by 30% compared to manual methods, while increasing plant growth by 20% in a three-month observation period. In addition, the solution supports local community participation with technical training, creating new economic opportunities through productive crop cultivation. This innovation is expected to become a sustainability model that can be replicated in other regions, integrating IoT technology in supporting resource efficiency, community empowerment, and environmental conservation. This research concludes that the application of IoT technology in community-based environmental management can accelerate the achievement of economic and ecological sustainability goals in tourist areas.